2017
DOI: 10.12681/bgsg.15004
|View full text |Cite
|
Sign up to set email alerts
|

Geological and seismological evidence for NW-SE crustal extension at the southern margin of Heraklion basin, Crete.

Abstract: In this paper we present new geological and seismological data on the orientation of crustal extension in central Crete (SE Heraklion basin) following the occurrence of two shallow seismic sequences: a) the May 2005 Assimi M=4.1 earthquake sequence and b) the 2013 Houdetsi-Tefeli sequence (3.2≤Mw≤3.6). Emphasis is given to the results of the geological field work, stress analysis, source inversion, aftershock relocations and mapping of earthquake-induced environmental effects. For the first time we find seismo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Upper-Plate Faults and their Context Within a Converging Zone While thrust faulting dominates the offshore of southern Crete at depths above and along the subduction interface, shallower depths of <15 km and closer to the southern shoreline of Crete are predominantly characterized by normal and transtensional faulting (Alves et al, 2007;Kokinou et al, 2012;Papazachos, 1990;Ten Veen & Kleinspehn, 2003). Onshore, normal faulting is prevalent, with the strikes of these dip-slip faults having multiple directions suggesting a complex extensional regime (Caputo et al, 2010;Ganas et al, 2017;Mercier et al, 1987;Zygouri et al, 2016). The active normal faults broadly trend E-W or N-S with the exception of the Ierapetra and Kastelli faults, which trend NE-SW (Strobl et al, 2014) (Figure 1a).…”
Section: 1029/2018tc005410mentioning
confidence: 99%
See 1 more Smart Citation
“…Upper-Plate Faults and their Context Within a Converging Zone While thrust faulting dominates the offshore of southern Crete at depths above and along the subduction interface, shallower depths of <15 km and closer to the southern shoreline of Crete are predominantly characterized by normal and transtensional faulting (Alves et al, 2007;Kokinou et al, 2012;Papazachos, 1990;Ten Veen & Kleinspehn, 2003). Onshore, normal faulting is prevalent, with the strikes of these dip-slip faults having multiple directions suggesting a complex extensional regime (Caputo et al, 2010;Ganas et al, 2017;Mercier et al, 1987;Zygouri et al, 2016). The active normal faults broadly trend E-W or N-S with the exception of the Ierapetra and Kastelli faults, which trend NE-SW (Strobl et al, 2014) (Figure 1a).…”
Section: 1029/2018tc005410mentioning
confidence: 99%
“…These studies show that thrust faulting occurs as a result of forearcnormal compression at depths linked to subduction to the south of Crete; additionally, Shaw et al (2008) suggested that reverse (high-angle) splay faults may cut the upper crust in western Crete; however, their existence was debated by Ganas and Parsons (2009) on the basis of a lack of compatible seismological data. The E-W and N-S trending normal faults accommodate arc-normal and arc-parallel extension (Angelier, 1979a;Armijo et al, 1992;Caputo et al, 2006;Caputo et al, 2010;Fassoulas, 2000;Floyd et al, 2010;Gallen et al, 2014;Gallen & Wegmann, 2016;Ganas et al, 2017;Howell et al, 2017;Kokinou et al, 2012;Peterek & Schwarze, 2004;Snopek et al, 2007), which is also reflected in Eurasian (upper) plate GPS motions that increase toward the southern edge of the plate in the location of Crete (Floyd et al, 2010;McClusky et al, 2000) and are quantified by Nocquet (2012) as~10 mm/year. Pleistocene uplift is visible in sequences of preserved marine terraces seen throughout the eastern and southern coasts of Crete (Angelier, 1979b;Gaki-Papanastassiou et al, 2009;Gallen et al, 2014;Peterek & Schwarze, 2004;Pirazzoli et al, 1982;Strobl et al, 2014).…”
Section: 1029/2018tc005410mentioning
confidence: 99%
“…While thrust faulting dominates the offshore of southern Crete at depths above and along the subduction interface, shallower depths of <15 km and closer to the southern shoreline of Crete are predominantly characterized by normal and transtensional faulting Confidential manuscript submitted to Tectonics (Alves et al, 2007;Kokinou et al, 2012;Papazachos, 1990;Ten Veen and Kleinspehn., 2003). Onshore, normal faulting is prevalent, with the strikes of these dip-slip faults having multiple directions suggesting a complex extensional regime (Caputo et al, 2010;Ganas et al, 2017;Mercier et al, 1987;Zygouri et al, 2016). The active normal faults broadly trend E-W or N-S with the exception of the Ierapetra and Kastelli faults which trend NE-SW (Strobl et al, 2014) (Figure 1a).…”
Section: Upper Plate Faults and Their Context Within A Converging Zonementioning
confidence: 99%
“…Observations from uplifted palaeoshorelines (e.g Gallen et al, 2014;(Mouslopolou et al, 2015a;Mouslopolou et al, 2015b;Pirazzoli et al, 1982;Shaw et al, 2008;Tsimi et al, 2007), Palaeolithic sites (Strasser et al, 2011), alluvial fans (Mouslopolou et al, 2017;Pope et al, 2008) and other geomorphological and biological features (Kelletat, 1991;Shaw et al, 2010) along its south and west coasts have been used to discuss the relationships between slip on the subduction interface, thrust faults in the overlying wedge, and historic tsunamigenic earthquakes (Ganas & Parsons, 2009;Shaw et al, 2008;Shaw & Jackson, 2010;Stiros, 2010). However, less attention has been given to the role of active normal faulting in Confidential manuscript submitted to Tectonics influencing uplift, a phenomenon that is widespread on Crete (Angelier, 1979a;Armijo et al, 1992;Caputo et al, 2010;Gallen et al, 2014;Ganas et al, 2017). The upper-plates of subduction zones throughout the World have been shown to host onshore and offshore uppercrustal normal faults (e.g: Binnie et al, 2016;Bottner et al, 2018;Cashman and Kelsey, 1990;Howell et al, 2016;McIntosh et al, 1993;McNeill et al, 1998;Meschis et al, 2018;Monaco and Tortorici, 2001;Wessel et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation